2021
DOI: 10.1109/access.2020.3028609
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Robust Adaptive Jaya (Ajaya) Based Maximum Power Point Tracking of a PV-Based Generation System

Abstract: When subjected to partial shading (PS), photovoltaic (PV) arrays suffer from the significantly reduced output. Although the incorporation of bypass diodes at the output alleviates the effect of PS, such modification results in multiple peaks of output power. Conventional algorithms-such as perturb and observe (P&O) and hill-climbing (HC)-are not suitable to be employed to track the optimal peak due to their convergence to local maxima. To address this issue, various artificial intelligence (AI) based algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…Otherwise, the newly updated solution will be generated. The flow chart of the Jaya algorithm applied to MPP tracking is shown in Figure 9, and its explanation is given below 47‐49 The population size ( n ) is chosen. Initial values of the candidate solution are chosen as fixed values. Fitness functions are evaluated. Convergence criteria are checked. Re‐initialization of the algorithm will take place in case of changing solar insolation. …”
Section: Nature‐inspired Optimization Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the newly updated solution will be generated. The flow chart of the Jaya algorithm applied to MPP tracking is shown in Figure 9, and its explanation is given below 47‐49 The population size ( n ) is chosen. Initial values of the candidate solution are chosen as fixed values. Fitness functions are evaluated. Convergence criteria are checked. Re‐initialization of the algorithm will take place in case of changing solar insolation. …”
Section: Nature‐inspired Optimization Algorithmsmentioning
confidence: 99%
“…Otherwise, the newly updated solution will be generated. The flow chart of the Jaya algorithm applied to MPP tracking is shown in Figure 9, and its explanation is given below [47][48][49] 1. The population size (n) is chosen.…”
Section: Jaya Algorithmmentioning
confidence: 99%
“…By doing so, we reduce the number of update equations to one that avoid searching useless regions and reduce computational burden. Finally, we evaluated the LBNS against two recently proposed algorithms we mentioned before ( [16] and [17]), and the results showed that it significantly outperforms them. In addition, the proposed solution reduction technique can be applied to other metaheuristic techniques to further improve their performance in MPP tracking.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this two-phase split, the global exploration and the convergence are improved compared to the simple Jaya algorithm. Moreover, in [17], another improved variant of the Jaya algorithm known as adaptive Jaya (AJaya) is proposed that uses varying iteration weighting coefficients in the Jaya update equations, improving the convergence speed of the simple Jaya algorithm and reducing the number of power fluctuations. Finally, in [18], a Most Valuable Player Algorithm (MVPA) algorithm uses a clever strategy based on the sensitivity of the Power versus Voltage and duty ratio to limit the search space to a set of solutions with a high probability of finding the global maximum there, and thus significantly improving the convergence speed and reducing the power losses.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, various artificial intelligent MPPT methodologies have been implemented to handle the shortcomings of the conventional MPPT methods, especially highly intermittent conditions. These include fuzzy logic control (FLC) [20], artificial neural network (ANN) [21], firefly algorithm (FA) [22], PSO [23], ant colony optimization (ACO) [24], flower pollination algorithm (FPA) [25], invasive weed optimization [26], salp swarm optimization [27], bat optimization [28], Neighboring-Pixel-based virtual imaging technique [29], surface-based polynomial fitting [30], Jaya algorithm [31], most valuable player algorithm [32] and many more. The results demonstrated that the artificial intelligence algorithms have high accuracy and stability in tracking the global MPP in different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%